Analisis Pengaruh Efektivitas Dan Risiko Keamanan Terhadap Minat Penggunaan Fintech (Studi Pada Anggota Komunitas Perempuan Girl Boss Indonesia) - Yasmin, Raisya A; Susyanti, Jeni; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Technological advancements have driven the rapid growth of financial technology (fintech), which has become increasingly popular as a solution to facilitate financial activities. Fintech offers convenience, efficiency, and accessibility, making it an essential tool in modern financial transactions. However, concerns regarding security risks remain a factor that may influence user adoption. This study aims to analyze the influence of effectiveness and security risk on the interest in using fintech, both simultaneously and partially. Employing a quantitative approach, data were collected from 105 respondents who are active members of the Girl Boss Indonesia community through a structured questionnaire. The data were analyzed using multiple linear regression to determine the relationships between the variables. The results indicate that effectiveness and security risk collectively have a significant impact on the interest in using fintech. Partially, effectiveness has a positive and significant influence on fintech adoption. Meanwhile, security risk has a positive but not significant influence on the interest in using fintech. Keywords: Effectiveness, Security Risk, Interest, Fintech